Plant glycosides and glycosidases: classification, sources, and therapeutic insights in current medicine - Kowsalya, Kumaresan; Vidya, Nandakumar; Halka, Jayachandran; Preetha, Jaganathan Sakthi Yazhini; Saradhadevi, Muthukrishnan; Sahayarayan, Jesudass Joseph; Gurusaravanan, Packiaraj; Arun, Muthukrishnan (Glycoconjugate journal, 2025)
Plant glycosides have a broad spectrum of pharmaceutical activities primarily due to the glycosidic residues present in their structure. Especially, the therapeutic glycosides can be classified into many compounds based on the sugar moiety, chains/ saccharide units, glycosidic linkages, and aglycones. Among many classes, the widely used pharmacological classification is based on the aglycones linked to the glycoside molecule. Based on these non-sugar moiety (aglycones), plant glycosides are further classified into twelve different types of glycosides along with the recent discovery of novel (cannabinoid) glycosides. They are called alcoholic, anthraquinone, coumarin, chromone, cyanogenic, flavonoid, phenolic, cardiac, saponin, thio, steviol, iridoid, and cannabinoid glycosides. Each of the plant glycosides has been discussed in this paper with, origin, structure, and abundant presence in a specific family of plants. Besides, the therapeutic roles of these plant glycosides are further described in detail to validate their efficacies in the human health care system. On the other hand, glycosides are inactive until enzymatic hydrolysis releases their active aglycone, enabling targeted drug delivery. This process enhances aglycone solubility and stability, improving bioavailability and therapeutic efficacy. They target specific receptors or enzymes, minimizing off-target effects and enhancing pharmacological outcomes. Derived from plants, glycosides offer diverse chemical structures for drug development. They are integral to traditional medicine and modern pharmaceuticals, utilized in therapies ranging from cardiology to antimicrobial treatments. Graphical abstract